2015
DOI: 10.1016/j.eururo.2014.08.074
|View full text |Cite
|
Sign up to set email alerts
|

Long-term Health-related Quality of Life After Primary Treatment for Localized Prostate Cancer: Results from the CaPSURE Registry

Abstract: a v a i l a b l e a t w w w . s c i e n c e d i r e c t . c o m j o u r n a l h o m e p a g e : w w w . e u r o p e a n u r o l o g y . c o m Outcome measurements and statistical analysis: The Medical Outcomes Studies 36-item Short Form and the University of California, Los Angeles, Prostate Cancer Index characterized physical function, mental health, and sexual, urinary, and bowel function and bother. Repeated measures mixed-model analysis assessed change in HRQOL by treatment over time, and logistic regressi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
142
3
7

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 172 publications
(161 citation statements)
references
References 17 publications
9
142
3
7
Order By: Relevance
“…Data on health-related quality of life after treatment can also be analyzed. Sexual dysfunction and urinary incontinence and/or irritative symptoms are common long-term sequelae after PCa treatment [35,95]. Since the incidence of erectile dysfunction and urinary incontinence may vary substantially according to definition, the use of patient-reported outcomes and validated questionnaires is preferred [96][97][98][99][100].…”
Section: 4mentioning
confidence: 99%
See 1 more Smart Citation
“…Data on health-related quality of life after treatment can also be analyzed. Sexual dysfunction and urinary incontinence and/or irritative symptoms are common long-term sequelae after PCa treatment [35,95]. Since the incidence of erectile dysfunction and urinary incontinence may vary substantially according to definition, the use of patient-reported outcomes and validated questionnaires is preferred [96][97][98][99][100].…”
Section: 4mentioning
confidence: 99%
“…Long-term oncologic outcomes for combined ADT in stage IV PCa [32] Prospective patient registries CaPSURE: UCSF Cancer of the Prostate Strategic Urologic Research Endeavor Development and validation of the CAPRA score to predict pathologic and biochemical outcomes after RP [129] Time trends and variation in primary treatment of PCa in the USA [130] Long-term health-related quality-of-life outcomes after PCa treatment [95] Comparative effectiveness of RP, radiotherapy, and ADT in patients with clinically localized PCa [89] Impact of ADT on physical, mental, and emotional wellbeing in PCa patients [131] Association between race and the likelihood of upgrading, upstaging, and positive surgical margins at RP [132] Cost burden of PCa according to treatment type [106] MUSIC: Michigan Urological Survey Improvement Collaborative…”
Section: Caesar: Comparative Effectivenessmentioning
confidence: 99%
“…Multiple studies, including data from the U.S. CaPSURE registry, have shown that radical prostatectomy patients are more likely to suffer from urinary incontinence than radiotherapy patients and are also more likely to have higher rates of impotency, although both groups report high erectile dysfunction rates (62-94%) [31][32][33][34]. Complications related to bowel function affect individuals treated by both radical prostatectomy and radiotherapy, but radiotherapy patients have been indicated to experience more significant declines [32][33][34].…”
Section: Curative Treatmentmentioning
confidence: 99%
“…However, multiple studies have revealed that while no significant difference in overall health-related quality of life exists between prostate cancer patients who have undergone radical prostatectomy and age-adjusted controls, the sexual, bowel, and urinary functions of radical prostatectomy patients have declined more substantially than that of controls [36][37][38][39]. Multi-model treatment and particularly the use of androgen deprivation therapy have been associated with the highest risk of adverse effects and the greatest impairment to physical function [34,39,40].…”
Section: Curative Treatmentmentioning
confidence: 99%
“…Their choice of cohorts to include, moreover, was far from inclusive and overemphasized outdated studies, thus leading to overestimation of the harms. The inadequacy of the literature review on this question is evident, for example, in the selection of references for the PCOS and CaPSURE cohorts which were over a decade out of date relative to more recent papers [19,20]. Cohorts such as PROST-QA [21] were excluded entirely, as were large meta-analyses [22][23][24][25] and other data sources.…”
mentioning
confidence: 99%